Constantine : history, historiography, and legend - Lieu, Samuel N. C.; Montserrat, Dominic, 1964- (Routledge, 1998)
Constantine: History, Historiography and Legend examines the reign of Constantine, the first Christian emperor and the founder of Constantinople, from a variety of angles: historical, historiographical and mythical.